DEVELOPING INTERACTIVE VIDEOS FOR FACILITATING READING ACTIVITY IN AN INCLUSIVE CLASS AT THE SIXTH GRADE OF SDN 2 BENGKALA - Cahya Putri, Ida Ayu Cantika; Utami, I G A Lokita Purnamika; Adi Ana, I Ketut Trika (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2025)
This study aims to develop interactive videos to support sixth-grade students in an inclusive classroom at SDN 2 Bengkala with their reading tasks. Particularly for pupils with exceptional needs, including deaf and mute learners, inclusive education poses additional difficulties. These difficulties emphasize the necessity for creative instructional resources catered to a range of learning capacities and styles. The ADDIE model, which has phases for analysis, design, development, implementation, and evaluation, is followed in the development process. The primary goal of the study is to identify the specific needs of students in inclusive classrooms, create interactive video to satisfy those needs, and evaluate the usefulness and content validity of the final products. The findings of the study emphasize the importance of visual and auditory elements in enhancing students' engagement and reading comprehension. The results help close the gap in educational possibilities for all children by providing a paradigm for developing interesting and easily available learning resources. Additionally, this study emphasizes how technology may help create a fair and inclusive learning environment so that children with special needs can get high-quality instruction.